THE EFFECTIVENESS OF TAHFIDZUL QUR’AN LEARNING IN ENHANCING STUDENTS' SPIRITUAL INTELLIGENCE AT MTs INSAN QUR’ANI RANULOGONG - Maziyah, Fiki Khofi; Muttaqin, Ahmad Ihwanul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Memorizing the Qur’an is a challenging task that requires dedication, discipline, and high commitment. Hafiz (memorizers of the Qur’an) are considered individuals chosen by Allah. In the modern era, challenges are even greater due to instant lifestyles and free social interactions, which can be distracting, especially for teenagers. The author chose MTs Insan Qur’ani in Ranulogong as the research site because this Islamic boarding school has well-organized religious activities that help foster a disciplined lifestyle and shape a balanced personality between academic and religious needs. The research focuses in this study are: 1) How is the process of Tahfidz Al-Qur’an learning for students at MTs Insan Qur’ani in Ranulogong? 2) How effective is the Tahfidzul Qur’an learning in enhancing students' spiritual intelligence at MTs Insan Qur’ani in Ranulogong? Based on these focuses, the objectives of this study are: 1) To analyze the process of Tahfidz Qur’an learning for students at MTs Insan Qur’ani in Ranulogong. 2) To examine the effectiveness of Tahfidzul Qur’an learning in enhancing students' spiritual intelligence at MTs Insan Qur’ani in Ranulogong.The method used in this research is descriptive field research with a qualitative approach. The data collection techniques employed by the researcher include observation, interviews, and documentation. The findings of this study can be concluded as follows: 1) The Tahfidz learning process at MTs Insan Qur’ani in Ranulogong has demonstrated a high level of effectiveness in Qur’an memorization, with students achieving results that reflect their commitment and effort in completing their memorization. 2) The research findings indicate a significant improvement in students' spiritual intelligence, particularly in their daily lives, after participating in the Tahfidz Qur’an learning program at MTs Insan Qur’ani in Ranulogong.